The Influence of Internship Experience, Soft Skills, and Hard Skills on Work Readiness - Pramestie, Naomi Nindya; Prabowo, Budi (Publik : (Jurnal Ilmu Administrasi), 2025)
The purpose of this study is to examine the impact of internship experience, interpersonal skills, and technical skills on the work readiness level of students at LP3I College Surabaya. This study is based on the urgent need for higher education graduates to be prepared for the challenges of the world of work, not limited to technical skills alone, work experience, and interpersonal skills are also very important factors. This research design is quantitative and uses an associative approach. The study involved 42 students as samples from the 2023–2025 cohort who had participated in an internship program. The study employed a saturated sampling technique for sample selection, and data analysis was performed using multiple linear regression techniques through the SPSS version 31 application. The findings show that, simultaneously, internship experience, interpersonal skills, and technical skills have a positive and significant impact on work readiness. Partially, it was found that internship experience and interpersonal skills contributed positively to the work readiness of LP3I College Surabaya students significantly, while hard skills did not show a meaningful influence. These findings indicate that the employability of LP3I College Surabaya students is determined more by real-world internship experience and non-technical skills than by technical skills alone.